2006
DOI: 10.1161/circulationaha.105.001107
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Intracoronary Infusion of Mobilized Peripheral Blood Stem Cells by Granulocyte Colony–Stimulating Factor on Left Ventricular Function and Remodeling in Patients With Acute Myocardial Infarction Versus Old Myocardial Infarction

Abstract: Background-The efficacy of intracoronary infusion of granulocyte colony-stimulating factor (G-CSF) mobilized peripheral blood stem cells (PBSCs) has not been compared between patients with acute (AMI) versus old myocardial infarction (OMI). In addition, the potential risk of restenosis associated with G-CSF-based stem cell therapy has not been evaluated in the setting of drug eluting stent (DES) implantation. Methods and Results-We randomly allocated 96 patients with myocardial infarction who underwent coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
134
5
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 30 publications
3
134
5
4
Order By: Relevance
“…Myocardial infarction leads to the loss of cardiomyocytes, followed by pathological LV remodeling and progression Jin-Ho Choi [30] Huikuri HV [29] Meluzin J(Low) [28] Meluzin J(Hi) [28] MAGIC Cell-3-DES [27] Janssens S [25] BOOST (18) [24] BOOST(6) [24] Li Zhan-quan [23] REPAIR-AMI [21] Study ID Figure 3. Effects of stem cell therapy compared with standard treatment on changes in LVESV in post-AMI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial infarction leads to the loss of cardiomyocytes, followed by pathological LV remodeling and progression Jin-Ho Choi [30] Huikuri HV [29] Meluzin J(Low) [28] Meluzin J(Hi) [28] MAGIC Cell-3-DES [27] Janssens S [25] BOOST (18) [24] BOOST(6) [24] Li Zhan-quan [23] REPAIR-AMI [21] Study ID Figure 3. Effects of stem cell therapy compared with standard treatment on changes in LVESV in post-AMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…No heterogeneity for this outcome was found (heterogeneity test: I 2 = 29.8%, P = 0.162). ASTAMI [22] li Zhan-quan [23] BOOST(6) [24] BOOST (18) MAGIC Cell-3-DES [27] Meluzin J(Hi) [28] Meluzin J(Low) [28] Huikuri HV [29] Jin-Ho Choi [30] José Suárez [31] −58 58 0 Overall (I-Squared = 1.1%, p = 0.435) Subgroup analysis by RCT/non-RCT was performed to investigate whether this feature of study design would influence the effectiveness of cell therapy. No significant differences in effect size between RCT and non-RCT studies were found (test of heterogeneity between groups: for LVEDV, P = 0.445; for LVESV, P = 0.794; Table 2).…”
Section: Effect Of Intracoronary Cell Therapy On Changes In Lvedv Andmentioning
confidence: 99%
“…The first randomized, double blind, and placebo-controlled study on CPC transplantation demonstrated an improvement in coronary flow reserve, decline in the number of hibernating segments, and an increase in LVEF at 3 months after transplantation, indicating that CPC transplantation was effective for OMI patients [62]. Contrary to this finding, The MAGIC cell-3DES randomized and controlled trial revealed that, although CPC transplantation had a positive impact on cardiac performance in AMI patients, it had no effect on OMI patients [63]. Assumus et al supported these results in his paper [49].…”
Section: Other Clinical Studies In Cellular Cardiomyoplastymentioning
confidence: 91%
“…Then the investigators changed the design and used drug-eluting stents. In the MAGIC 3-DES trial, positive results in terms of LVEF were found after mobilization and intracoronary injection of isolated cells (Kang et al, 2006). Table 2.…”
Section: Stem Cell Therapy After Acute Myocardial Infarctionmentioning
confidence: 99%